2019
DOI: 10.3390/su12010197
|View full text |Cite
|
Sign up to set email alerts
|

What is Interdisciplinarity in Practice? Critical Reflections on Doing Mobility Research in an Intended Interdisciplinary Doctoral Research Group

Abstract: Lately, there has been a tendency in academia to call for more interdisciplinary research on sustainable mobility. However, there is a lack of empirical research on practiced interdisciplinarity. This paper seeks to address this by exploring the practices of an intended interdisciplinary doctoral research group. Specifically, it presents the study of a collaborative autoethnography using individual vignettes and qualitative data analysis. The results classify the identified interdisciplinary practices into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…These factors include the social and relational climate that inform people's inter-personal work environment and their daily social interactions, the broader institutional environment and structure, such as policies and procedures governing their work, as well as the expectations they face and the resources that are available to them within a high pressure environment that is managed through a complex bureaucracy. Our research echoes findings by Villeneuve and colleagues [35] who have also recently explored the relationship between interdisciplinary team building and wicked problems. Similar to our theme on the importance of a positive social and relational climate for supporting iQoL, they found that the nature of interdisciplinary interactions could generate advantages or challenges as related to the intersubjective relationships between team members [35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These factors include the social and relational climate that inform people's inter-personal work environment and their daily social interactions, the broader institutional environment and structure, such as policies and procedures governing their work, as well as the expectations they face and the resources that are available to them within a high pressure environment that is managed through a complex bureaucracy. Our research echoes findings by Villeneuve and colleagues [35] who have also recently explored the relationship between interdisciplinary team building and wicked problems. Similar to our theme on the importance of a positive social and relational climate for supporting iQoL, they found that the nature of interdisciplinary interactions could generate advantages or challenges as related to the intersubjective relationships between team members [35].…”
Section: Discussionsupporting
confidence: 88%
“…Our research echoes findings by Villeneuve and colleagues [35] who have also recently explored the relationship between interdisciplinary team building and wicked problems. Similar to our theme on the importance of a positive social and relational climate for supporting iQoL, they found that the nature of interdisciplinary interactions could generate advantages or challenges as related to the intersubjective relationships between team members [35]. Building on our findings, universities could promote supportive social and relational climates, ensure that adequate time is given and infrastructure is in place to conduct research, and provide adequate resources, among other initiatives to support iQoL among its employees and students.…”
Section: Discussionsupporting
confidence: 88%
“…In order to avoid this, we have, as Adams, Jones and Ellis [44] suggest, discussed our own self reflections within the research group and, thus, found intersections between self, group and society, as well the personal and political. We have, thus, attempted a collective autoethnography aimed at collective meaning-making [45]. This process is also an inductive research process, meaning that, while observing and researching, we analyze and formulate our theory.…”
Section: Methodsmentioning
confidence: 99%
“…There are possibilities to generate interactive communication from Scaffolding through the idea of collaboration as a group. Villeneuve et al (2019) acknowledged that to add more value to a real-world situation for practice, students that are set under a genuine practice develop a sort of diverse culture, with distinctive skills, backgrounds, and worldviews that are necessary for the students to admit to being successful. This kind of implementation remains different from the cultural type of class activity, where efforts in setting all information is a sole impression, to that of college (Dincer, Yesilyurt, Noels, & Vargas Lascano 2019).…”
Section: Models Integrationmentioning
confidence: 99%